ABO and Rh-D blood group frequency and distribution: a tertiary care hospital experience - Sanagapati, Pandu Rangarao; Vujhini, Sudhir Kumar (International Journal of Research in Medical Sciences, 2017)
Background: This study was carried out to determine the frequency and distribution of ABO and Rhesus (Rh) blood groups in blood donors of tertiary care hospital-attached blood bank. Methods: This study was conducted among the blood donors of Hyderabad Telangana State (India), who donated blood during the period from July 2013 to December 2014. ABO and Rh blood grouping was performed by forward blood grouping (cell grouping) using test tube agglutination method using antisera A, antisera B and antisera D and by reverse grouping using pooled known A, B and O cells. Results: Out of 1740 blood donors, 1702 (55.6%) were male and 38 (44.4%) were female. Majority of blood donors were in 21-40 years of age group. The most frequent blood group positions in the descending order are ‘O’, ‘A’, ‘B’ and ‘AB’ respectively. One group was ‘Oh’ (Bombay Phenotype). Conclusions: ‘O’ group is the most frequent position of ABO blood group system followed by ‘A’ group. Rh+ is the most frequent group than Rh- in the Rh system. Blood donations by females are very low.